Retrorectal Schwannoma (Revista Argentina de Cirugía, 2021)
Retrorectal tumors are rare but have potential malignant transformation and risk of infection. Thet are usually asymptomatic. We report the case of a 62-year-old female patient with chronic pelvic pain and imaging tests showing a 3-cm space-occupying lesion in the presacral region. The lesion resected and the histopathologic diagnosis was schwannoma.
Keywords: retrorectal tumors; schwannoma; magnetic nuclear resonance; resection